a, b, c gives
a=1/2, b=1/2, c=1
Thus Rn =1/2n²+1/2n+1
When n=5, R5=1/2*5^2+1/2*5+1=16, which is also corresponds to the tabulated value for n=5 above.
Rn =1/2n²+1/2n+1 is the same with Rn=(n^2+n+2)/2
So far we have formed a conjecture that the maximum number of regions from n-chords is given by R= (n^2+n+2)/2.
Proof:
Let P(n) be the proposition that the maximum number of regions that can be separated from n-chords is given by R= (n^2+n+2)/2 for n0
Step1: P(n) is true for n=1 as R= (1^2+1+2)/2=2 which is the maximum number of regions from 1 chord.
Step2: Assume that P(n) is true for a k-chords circle i.e., that Rk= (k^2+k+2)/2. We consider the effect that adding an extra cut will have on the result.
Step3: Looking at the tabulated value for n and R, you will found that adding an extra chord to a circle produces an extra (n+1) regions, so that we can say that
Rk+1=Rk+ the extra regions added by the extra chords.
=Rk+ (k+1)
= (k^2+k+2)/2+ (k+1)
= (k^2+3k+4)/2
Step4: (k^2+3k+4)/2 is theassertion
Therefore, if the proposition is true for n=k, then it is true for n=k+1. As it is true for n=1, then it must be true for n=1+1=2. As it is true for n=2 then it must hold for n=2+1=3 and so on for all integers n0.
That is, by the principle of mathematical induction. P(n) is true.
Now we try to rewrite the formula in the form R=X+S, when X is an algebraic expression in n:
Compare these two tables, we can find out that
R2=R1+S1=2+2=4
R3=R2+S2=4+3=7
R4=R3+S3=7+4=11
R5=R4+S4=11+5=16
Thus R=X+ (n+1) X=R-(n+1) X= (n^2-n)/2
Therefore, R=X+S= (n^2-n)/2+ (n+1)
①Recursive rule:
P1=2=R1
P2=4=2+2= R1+P1
P3=8=4+4= R2+P2
P4=15=7+8= R3+P3
P5=26=11+15= R4+P4
Thus Pn= Pn-1+Rn-1
= Pn-2+ Rn-2+……+Rn-1
=Pn-(n-1) +Rn-(n-1) + Rn-2+……+ Rn-1
=P1+R1+ R2+ R3+……+ Rn-1
= 2+(1^2+1+2)/2+(2^2+2+2)/2 +……+ (n^2+n+2)/2
= 2+(n-1)+[1*2+2*3+3*4+……+n*(n-1)]/2
= n+1+ (n-1)*n*(n+1)]/ (3*2)
= (n^3+5n+6)/6
Therefore, the recursive rule to generate the maximum number of parts is
(n^3+5n+6)/6
When n=5, P5= (5^3+5*5+6)/6=16, which corresponds to the tabulated value for n=5 above.
②A conjecture for the relationship between the maximum number of parts(P) and the number of cuts(n).
Use TI-84 to sketch the
graph related to the variables n and P
suggests that the relationship between
them could be cubic, and so we
might assume that
P=an³+bn²+cn+d
Substituting all the values for
n gives:
n=12=a+b+c+d
n=24=8a+4b+2c+d
n=38=27a+9b+3c+d
n=415=64a+16b+4c+d
n=526=125a+25b+5c+d
Solve these five equations for
a, b, c, d gives
a=1/6, b=0, c=5/6, d=1
Thus Pn =1/6n³+5/6n+1
When n=5, P5=1/6*5³+5/6*5+1, which is also corresponds to the tabulated value for n=5 above.
Pn = (n^3+5n+6)/6 is the same with Pn =1/6n³+5/6n+1
So far we have formed a conjecture that the maximum number of parts from n-cuts is given by Pn = (n^3+5n+6)/6.
Proof:
Let T(n) be the proposition that the maximum number of parts that can be separated from n-cuts is given by P= (n^3+5n+6)/6 for n>0
Step1: T(n) is true for n=1 as P= (1^3+5+6)/6=2 which is the maximum number of parts from 1 cut.
Step2: Assume that T(n) is true for a k-cuts cuboid i.e., that Pk= (k^3+5k+6)/6. We consider the effect that adding an extra cut will have on the result.
Step3: Looking at the tabulated value for n and P, you will found that adding an extra cut to a cuboid produces an extra (n^2+n)/2 parts, so that we can say that
Pk+1=Pk+ the extra parts added by the extra cuts.
=Pk+ (k^2+k+2)/2
= (k^3+5k+6)/6 + (k^2+k+2)/2
= (k^3+3k^2+8k+12)/6
Step4: (k^3+3k^2+8k+12)/6 is theassertion
Therefore, if the proposition is true for n=k, then it is true for n=k+1. As it is true for n=1, then it must be true for n=1+1=2. As it is true for n=2 then it must hold for n=2+1=3 and so on for all integers n>0.
That is, by the principle of mathematical induction. T (n) is true.
Now we try to rewrite the formula in the form P=Y+X+S where Y is an algebraic expression in n:
Compare these three tables, we can find out that
P2=R1+P1=2+2=4
P3=R2+P2=4+4=8
P4=R3+P3=7+8=15
P5=R4+P4=11+15=26
P=Y+X+S=Y+ (n^2-n)/2+ (n+1)
Y=P-(n^2-n)/2+ (n+1)
= (n^3+5n+6)/6-[(n^2-n)/2+ (n+1)]
= (n^3+5n+6)/6-(n^2+n+2)/2
= n^3-3n^2+2n
Therefore, P=Y+X+S= (n^3-3n^2+2n) + (n^2-n)/2+ (n+1)
Looking at the spreadsheet’s value of different dimensional object for n, form a difference array, you will found that
Sequence 26 15 8 4 2 (Three-dimensional)
differences 11 7 4 2 (Two-dimensional)
differences 4 3 2 (One-dimensional)
differences 1 1
As we found that all the dimensional objects separated into 2 parts when n=1, therefore when n=1, Q1=2. Use the difference array again to find out the results of the four-dimensional.
Sequences 57 31 16 8 4 2 (Four dimensional)
differences 26 15 8 4 2 (Three-dimensional)
differences 11 7 4 2 (Two-dimensional)
differences 4 3 2 (One-dimensional)
differences 1 1
The results is shown below in a table:
①A conjecture for the relationship between the maximum number of parts(Q) and the number of cuts(n) in a four-dimensional object. As it is a four= dimensional object, so we might assume that
Q=
Substituting all the values for
n gives:
n=12=a+b+c+d+e
n=24=16a+8b+4c+2d+e
n=38=81a+27b+9c+3d+e
n=416=256a+64b+16c+4d+e
n=531=625a+125b+25c+5d+e
n=657=1296a+216b+36c+6d+e
Solve these six equations for
a, b, c, d, e gives
a=1/24, b= -1/12, c=11/24, d=7/12, e=1
Thus Qn = .
When n=6, Q6==57 which is also corresponds to the tabulated value for n=6 above.
Proof:
Let W (n) be the proposition that the maximum number of parts that can be separated from n-cuts in a four-dimensional object is given by
Step1:W(n) is true for n=1 as
which is the maximum number of parts from 1 cut.
Step2: Assume that W(n) is true for a k-cuts four-dimensional boject i.e., that . We consider the effect that adding an extra cut will have on the result.
Step3: Looking at the tabulated value for n and P, you will found that adding an extra cut to a four-dimensional object produces an extra (n^3+5n+6)/6 parts, so that we can say that
Qk+1=Qk+ the extra parts added by the extra cuts.
=Qk+ (n^3+5n+6)/6
= + (n^3+5n+6)/6
= (n^4+2n^3+11n^2+34n+48)/24
Step4: (n^4+2n^3+11n^2+34n+48)/24 is theassertion
Therefore, if the proposition is true for n=k, then it is true for n=k+1. As it is true for n=1, then it must be true for n=1+1=2. As it is true for n=2 then it must hold for n=2+1=3 and so on for all integers n>0.
That is, by the principle of mathematical induction. W (n) is true.
Now we try to rewrite the formula in the form Q=Z+Y+X+S where Z is an algebraic expression in n:
Compare these four tables, we can find out that
Q2=P1+Q1=2+2=4
Q3=P2+Q2=4+4=8
Q4=P3+Q3=7+8=15
Q5=P4+Q4=11+15=26
Q=Z+Y+X+S=Z+ (n^3-3n^2+2n) + (n^2-n)/2+ (n+1)
Z=Q-(n^3-3n^2+2n) + (n^2-n)/2+ (n+1)
=-[ (n^3-3n^2+2n)+(n^2-n)/2+ (n+1) (n^3+5n+6)/6-(n^2+n+2)/2]
=(n^4-26n^3+71n^2-46n)/24
=Therefore, Q=Z+Y+X+S=(n^4-26n^3+71n^2-46n)/24 +(n^3-3n^2+2n)+(n^2-n)/2+ (n+1)
http://tieba.baidu.com/f?kz=280407483
Why can this formula be used?
Inappropriate notation for multiplication.
Wrong notation for “to the power of “
最好用规范的分数线的形式表示。使用公式编辑器或MATH TYPE。